Associations between Dependency Behavior and Management Ability in A Cross-Sectional Study of Mother who Care for Children with Avoidant Restrictive Food Intake Disorder - Yoyok Bekti Prasetyo; Alia Syamsudin; Faqih Ruhyanuddin; Edi Purwanto; Nursalam Nursalam; Rachmat Hargono; Ahsan Ahsan (Jurnal Keperawatan Padjadjaran, 2020)
ARFID phenomena commonly found on children are strongly dependent on parental behaviors. A dependency behavior shown by parents constitutes a specific behavior that helps the parents fulfill children’s needs. This kind of behavior will define a parental management ability in dealing with eating disorder phenomena on their children. This research, therefore, was set to analyze parental dependency behavior on parental management ability in dealing with eating disorder phenomena. A cross-sectional design was occupied to accommodate the research. A total of 245 families were selected to be the respondents, especially those who were taking care of children with ARFID. Data were collected using self-administered questionnaire. For descriptive data analysis, Manne-Whitney U test, one-way analysis of variance, Kruskal-Wallis, correlation product moment, and multiple linear regression were employed. Parental dependency behavior was closely related to parental management ability in dealing with eating disorder phenomena, especially in taking care of children with ARFID (r = 0.354; p = 0.000 < 0.05). This dependency behavior encompassed parents calming children down (with p = 0.000 < 0.05), giving hug to children (p = 0.000 < 0.05), listening to children (p = 0.001 < 0.05), solving children’s problems (p = 0.000 < 0.05) and fulfilling needs of food and drink (p = 0.000 < 0.05). On top of that, parental management ability in dealing with eating disorder occurrence was perceived referring to the result of multiple linear regression analysis, which was said to be mainly influenced by a predictor of parental dependency behavior in solving children’s problems (with β = 0.211; p = 0.001) and fulfilling children’s needs of food and drink (with β = 0.134; p = 0.047).Parental management ability in dealing with eating disorder was necessarily influenced by parental dependency behavior in solving children’s problems and fulfilling children’s needs of food and drink. Therefore, we suggest that nursing intervention be provided in respect of this case upon the population of families taking care of children with ARFID.